Offenders as Victims of Crime? An Investigation into the Relationship Between Criminal Behaviour and Victimisation - Deadman, Derek
In this paper we consider the association between victimisation and offending behaviour using data from the Youth Lifestyles Survey. We consider the impact of violent, non-violent and persistent offending on the probability of being a victim of violent and non-violent crime and find a positive association between these using univariate probit estimates. However, taking into account the endogenous nature of offending and victimisation via a bivariate probit model, we find that univariate estimates understate the association. We suggest that policy recommendations should only be based on the bivariate analysis of the association between offending and victimisation.